(untitled) (Swiss Medical Weekly, 2018)
INTRODUCTION Men facing prostate cancer screening and treatment need to make critical and highly preference-sensitive decisions that involve a variety of potential benefits and risks. Shared decision-making (SDM) is considered fundamental for “preference-sensitive” medical decisions and it is guideline-recommended. There is no single definition of SDM however. We systematically reviewed the extent of SDM implementation in interventions to facilitate SDM for prostate cancer screening and treatment. METHODS We searched Medline Ovid, Embase (Elsevier), CINHAL (EBSCOHost), The Cochrane Library (Wiley), PsychINFO (EBSCOHost), Scopus, clinicaltrials.gov, ISRCTN registry, the WHO search portal, ohri.ca, opengrey.eu, Google Scholar, and the reference lists of included studies, clinical guidelines and relevant reviews. We also contacted the authors of relevant abstracts without available full text. We included primary peer-reviewed and grey literature of randomised controlled trials (RCTs) reported in English, conducted in primary and specialised care, addressing interventions aiming to facilitate SDM for prostate cancer screening and treatment. Two reviewers independently selected studies, appraised interventions and assessed the extent of SDM implementation based on the key features of SDM, namely information exchange, deliberation and implementation. We considered bi-directional deliberation as a central and mandatory component of SDM. We performed a narrative synthesis. RESULTS Thirty-six RCTs including 19 196 randomised patients met the eligibility criteria; they were mainly conducted in North America (n = 28). The median year of publication was 2008 (1997–2015). Twenty-three RCTs addressed decision-making for screening, twelve for treatment and one for both screening and treatment for prostate cancer. Bi-directional interactions between healthcare providers and patients were verified in 31 RCTs, but only 14 fulfilled the three key SDM features, 14 had at least “deliberation”, one had “unclear deliberation” and two had no signs of deliberation. CONCLUSIONS There is significant variation in the extent of SDM implementation among studies addressing SDM for prostate cancer screening and treatment. Further evaluation of these results on patient outcomes, a standardised SDM definition and guidance for an effective implementation in several clinical settings are needed.